Shaping Professional Character Through Boarding School Culture: A Qualitative Case Study of Vocational Students in Indonesia - Yustina Sapan; Cahya Fajar Budi Hartanto; Ratna Puspitasari; Aliah Bagus Purwakania Hasan; Yonas Muanley (Sakura Digital Nusantara, 2026)
Purpose: This study aims to examine the role of boarding school culture in shaping the professional character of vocational students. Specifically, it explores how values, routines, and social interactions within boarding school environments contribute to the development of discipline, responsibility, work ethics, independence, and interpersonal skills essential for students’ readiness to enter the workforce. Methods: This research employs a qualitative case study approach conducted at a vocational boarding school. Data were collected through in-depth interviews with students, teachers, dormitory supervisors, and school administrators, complemented by participant observation and document analysis. The data were analyzed using thematic analysis to identify patterns and meanings related to character formation processes influenced by boarding school culture. Findings: The findings reveal that boarding school culture plays a significant role in shaping students’ professional character through structured daily routines, value internalization, role modeling by educators, and consistent social control within the dormitory setting. Practices such as collective worship, time management, shared responsibilities, and experiential learning foster students’ self-discipline, accountability, teamwork, independence, and ethical behavior. These character traits are consistently reflected in students’ attitudes toward learning and work-related activities, demonstrating alignment with vocational education objectives. Research Implications: The study provides empirical evidence that boarding school environments can serve as a strategic model for strengthening character-based vocational education by bridging the gap between technical skill development and professional character formation. Originality: This study offers a novel contribution by integrating boarding school culture with professional character development in vocational education, an area that remains underexplored in existing literature.